AB1027 The utility of lip biopsy in patients diagnosed of IPAF (interstitial pneumonia with autoimmune features). (15th June 2017) - Park, HS; Millan, P; Castillo, D; Millan, M; Moya, P; Magallares, B; Laiz, A; Diaz, C; Llobet, JM De; Castellvi, I
Abstract : Background: The European Respiratory Society/American Thoracic Society Task Force has defined a classification criteria for interstitial pneumonia with features of autoimmunity that does not accord to a specific systemic disease. This criteria combines clinical, serological and radiological domains. The clinical criteria does not include dry syndrome eventhough the serological criteria does include antiRo and antiLa antibodies. It is known that some patients with dry syndrome with antibodies negativity undertake lip biopsy to confirm Sjögren Syndrome (SS). Therefore lip biopsy could be useful to IPAF if SS is suspected. Objectives: Determine the utility of lip biopsy in patients with interstitial pneumonia that present symptoms suggestive of an autoimmune disease. Methods: Retrospective study of patients attended between june of 2010 and june of 2016 in a tertiary referral hospital was done. We included 23 Pneumology patients diagnosed of IPAF that were referred to Rheumatology clinic to rule out underlying connective disease. All patients had a complete immunologic study, two pulmonary function test including diffusion capacity of CO and a lip biopsy to confirm SS. The results of the lip biopsy was analysed with different variables. Epidemiologic data, blood test, pulmonary function test and pattern of ILD by high definition CT or lung biopsy were analysed. Changes in therapeutic decisions and pulmonary function test a year after the lip biopsy were also registered. To compare qualitative variables we used Chi Square test or Fisher exact test when necessary. The statistical significance was set up to p-value inferior to 0.05. Results: 16 of 23 patients with ILD met classification criteria of IPAF (69.6%). 12 were women (52.2%) with a median age of 77 (from 54 to 87 years). The findings of our group is summarised in table 1 . 9 lip biopsies confirmed SS (39.1%) and 7 changed treatment according to result (30.4%). No variables such as sex, smoking, previous lung disease, dry syndrome or Schirmer test showed relation with lip biopsy result. Previous treatment with corticosteroids did not seem to influence the results of lip biopsy eventhough it was not statistically significant (p-value 0.059). No relation with antinuclear antibody or acute phase reactants was observed either. Lip biopsy was most useful to diagnose SS for those with Usual Interstitial Pattern (p<0.02) among other patterns of ILD. Conclusions: Lip biopsy is a complementary examination to consider for IPAF. In our group the results were significant for UIP. Corticosteroid therapy did not seem influential to the results of lip biopsy eventhough it was not statistically significant. In 39.1% SS was diagnosed and in 30.4% treatment was changed according to results. Disclosure of Interest: None declared